ANALISIS HADIS AL-WALAD LI AL-FIRÄ€SY DENGAN METODE ASBÄ€B AL-WURÅªD, DAN PENALARAN LUGHAWIYAH - Zaki Satria (SYARIAH: Journal of Islamic Law, 2023)
The problem of the position of children born out of wedlock is a classic problem which is still interesting to study and discuss the benefits that will arise from the problems that will be faced in accordance with changing times. Basically, many parties want to study the benefits of the position of illegitimate children using the maqasid al-syari'ah method with the aim of protecting the child's life, living a decent life and growing well, and getting rights like children born in generally. In fact, children born out of wedlock, whether sirri marriage, li'an or adulterous children, are not assigned to their father or their father's family, which causes a child not to have equal rights compared to children in general. This study tries to examine from the perspective of analysis the asbÄb al-wurÅ«d al-hadÄ«ts, lughawiyah, ta'lÄ«liyah and istiá¹£lÄhiyah methods. With this analysis it is hoped that it can answer the problem and become a solution for the legal position of children born out of wedlock.